Development and justification of the profession graph military officers of tank units - Yurkova, Olha (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Background. The full-scale invasion of the Russian Federation on the territory of Ukraine has become the biggest challenge for the Ukrainian people since the independence of our state. This fact became a catalyst for the development of military science at both the theoretical and practical levels and led to changes in the training of military specialists of various branches and types of troops. To date, the unsolved problem is the development of occupational profiles for specialists in a number of military specialties, including tankers. The practical application of the occupational profile of a soldier of a tank unit would make it possible to improve the quality of professional and psychological selection measures, to improve training programs, which will significantly affect the quality of the personnel of the Armed Forces of Ukraine. The purpose of the article is the theoretical substantiation and practical development of the professional profile of a soldier of a tank unit. Methods. To establish the main definitions of the research, we used theoretical methods, such as: analysis, synthesis, generalization, systematization of scientific sources. The method of analyzing documents, instructions and regulations was used to determine the main components and characteristics of the professional profile of the military personnel of tank units. Also, our research was based on the empirical research we have already conducted on the psychological characteristics of the professional activity of the military personnel of tank units, which was carried out using the empirical method of an expert survey. Results. The basis for the development of the professionogram was: the results of a theoretical analysis of scientific sources, official documents of the professional activity of tank units, a psychological analysis of the professional activity of tankers and the results of the expert evaluation method, which made it possible to determine the main individual and psychological qualities of the military personnel of tank unit. Сonclusions. The proposed psychogram contains the following positions: general characteristics of the professional activity of the military personnel of tank units; a list of sanitary and hygienic conditions and safety rules of activity (sensory and motor field); negative factors of influence on military personnel during their professional activities (objective and subjective); professional traits of the military personnel of tank units; professionally important qualities of the military personnel of tank units (cognitive, motivational, emotional and volitional, functional spheres and individual psychological qualities); a list of possible errors in the specialist's work; contraindications to the profession.
Keywords: professional activity, professionogram, psychogram, professional activity, military personnel of tank units